WAYS TO SOLVE BARRIERS TO INTEGRATING STEM EDUCATION INTO INFORMATICS TEACHER TRAINING - Maratova T.Ф.; Bostanov Б.Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This study is based on a quantitative method, which involved 129 informatics teachers (51 men and 78 women) from 43 schools in Almaty. The purpose of this study is to learn about barriers and ways to solve them for the implementation of integrated STEM (science, technology, engineering and mathematics) education in the training of future informatics teachers. The results of the study can be used in the development of educational programs in higher education institutions, which will lead to an improvement in the training of future informatics teachers. Despite research on the benefits and strategies of STEM education, barriers and solutions to its implementation, especially from the point of view of teachers, may be less clear. In the process of training future informatics teachers, there are various obstacles with limited access to resources, insufficient teacher training, lack of time and funds for retraining. These barriers include personal, institutional, and systemic issues that may hinder the integration of STEM into teaching practice. The study identifies these gaps and highlights the need to eliminate barriers to improving the quality of education in informatics and in the training of future computer science teachers.